2017
DOI: 10.1016/j.ymthe.2017.03.037
|View full text |Cite
|
Sign up to set email alerts
|

A Basic ApoE-Based Peptide Mediator to Deliver Proteins across the Blood-Brain Barrier: Long-Term Efficacy, Toxicity, and Mechanism

Abstract: We have investigated delivery of protein therapeutics from the bloodstream into the brain using a mouse model of late-infantile neuronal ceroid lipofuscinosis (LINCL), a lysosomal disease due to deficiencies in tripeptidyl peptidase 1 (TPP1). Supraphysiological levels of TPP1 are delivered to the mouse brain by acute intravenous injection when co-administered with K16ApoE, a peptide that in trans mediates passage across the blood-brain barrier (BBB). Chronic treatment of LINCL mice with TPP1 and K16ApoE extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
3
19
1
Order By: Relevance
“…With a demonstrated ability to transport compounds across the blood-brain barrier, this peptide has great potential (Sarkar et al, 2011(Sarkar et al, , 2014Meng et al, 2014Meng et al, , 2017 but, the toxicity of the peptide must be resolved. Although AChE is not the primary toxicity mechanism of action, it clearly plays a role.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With a demonstrated ability to transport compounds across the blood-brain barrier, this peptide has great potential (Sarkar et al, 2011(Sarkar et al, , 2014Meng et al, 2014Meng et al, , 2017 but, the toxicity of the peptide must be resolved. Although AChE is not the primary toxicity mechanism of action, it clearly plays a role.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of Late-infantile neuronal ceroid lipofuscinosis (LINCL) with deficiency in the lysosomal protease tripeptidyl peptidase I (TPPI) (Sleat et al, 1997(Sleat et al, , 2004, we have achieved supraphysiological levels (~800% of wild-type) of intravenously-administered recombinant TPP1 throughout the brain upon co-injection with K16ApoE. Furthermore, the mice demonstrated a significant improvement in neurological function and increased lifespan in either acute or chronic treatment with the mixture of TPP1 and K16ApoE (Meng et al, 2014(Meng et al, , 2017.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Likewise, the pulsed ultrasound and AAV based approaches have unknown long-term health implications. Interestingly, a 20 amino acid stretch of the APOE protein itself has been successfully utilized for shuttling therapeutics across the BBB in a mouse model of lipofuscinosis, a pediatric neurodegenerative disorder [222,223], suggesting the possibility of using endogenous shuttling signals for efficacious delivery through the BBB. Even with these exciting breakthroughs, several challenges remain: if administered peripherally, how do we prevent the APOE therapeutic to be titered by the peripheral pools of APOE, or worse, cause systemic metabolic dysfunction and additionally, how to safely guide the therapeutic to the affected brain regions or cell types once inside the brain.…”
Section: Critical Challenges For Targeting Cns Resident Apoementioning
confidence: 99%
“…Apart from hyperosmotic and vasoactive agents, little is known about other classes of molecules capable of intra-arterial BBBO. Previous studies have shown that systemic injection of membrane active peptides (MAPs) has the potential for permeabilizing biological barriers, including the BBB [21][22][23]. Importantly, MAP sequences can be engineered with customizable pharmacological properties (i.e.…”
Section: Introductionmentioning
confidence: 99%